1996
DOI: 10.1007/bf00226329
|View full text |Cite
|
Sign up to set email alerts
|

A limited sampling method to estimate methotrexate pharmacokinetics in patients with rheumatoid arthritis using a Bayesian approach and the population data modeling program P-PHARM

Abstract: This paper describes a methodology to calculate methotrexate (MTX) pharmacokinetic parameters after intramuscular administration using two samples and the population parameters. Total and free MTX were measured over a 36-h period in 56 rheumatoid arthritis patients; 14 patients were studied after a two-dose scheme at 15-day intervals. The Hill equation was used to relate the free MTX to the total MTX changes in plasma concentrations, and a two-compartment open model was used to fit the total MTX plasma concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…This is because fluctuations in the pharmacokinetics (e.g., a delay in absorption or elimination) resulting from any comedication 9 may change the outcome of the analyses. In this investigation, although the mean volume of the central compartment (V d ) was smaller than that in other reports (range 25.2-34.8 l), [6][7][8] we consider that this result was derived from the difference in the average body weight of the subjects (range 64.2-75 kg). [6][7][8] To date, no report has shown a definite correlation between the efficacy and the pharmacokinetics of MTX in the treatment of RA.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This is because fluctuations in the pharmacokinetics (e.g., a delay in absorption or elimination) resulting from any comedication 9 may change the outcome of the analyses. In this investigation, although the mean volume of the central compartment (V d ) was smaller than that in other reports (range 25.2-34.8 l), [6][7][8] we consider that this result was derived from the difference in the average body weight of the subjects (range 64.2-75 kg). [6][7][8] To date, no report has shown a definite correlation between the efficacy and the pharmacokinetics of MTX in the treatment of RA.…”
Section: Discussioncontrasting
confidence: 66%
“…However, this method is less convenient and entails higher costs. Bressolle et al 7 reported a method to estimate individual pharmacokinetic variables for MTX using a Bayesian method with two plasma concentration measurements, taken 2 h and 8 h after drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTX excretion depends solely on the kidney, and clearance rates have been reported to be 43% 1 h after administration, 88% 6 h after, and 100% (completely excreted) 24 h after in cases with normal renal function [20]. Significant correlation between creatinine clearance (CrCl) level and MTX clearance rate has been reported [21][22][23][24]. Delayed clearance is associated with myelotoxicity induced by chemotherapy in the high-dose MTX regimen [25].…”
Section: Discussionmentioning
confidence: 97%
“…[14] This study demonstrated that age explained a significant part (16.8%) of the interindividual variability in estimates of clearance. The age range of the patients in this study was 24 to 70 years.…”
Section: Pharmacokinetics Pharmacodynamics and Agingmentioning
confidence: 94%